Hoot - Hiaasen, Carl. (New York : Yearling, 2006)
Roy, who is new to his small Florida community, becomes involved in another boy's attempt to save a colony of burrowing owls from a proposed construction site.
"A Yearling book.".
Young Adult
Keywords: Burrowing owl -- Juvenile fiction; Environmental protection -- Juvenile fiction; Burrowing owl -- Fiction; Environmental protection -- Fiction; Owls -- Fiction; Burrowing owls -- Fiction; Environmental protection -- Fiction; Owls -- Fiction; Florida -- Juvenile fiction; Florida -- Fiction; Florida -- Fiction